Myo-Inositol as a Key Supporter of Fertility and Physiological Gestation - Riccardo Gambioli; Gianpiero Forte; Giovanni Buzzaccarini; Vittorio Unfer; Antonio Simone Laganà (MDPI AG, 2021)
Pregnancy is a complex process, featuring several necessary changes in women's physiology. Most women undergo healthy pregnancies; even so, several women experience reduced fertility or pathologies related to the pregnancy. In the last years, researchers investigated several molecules as promoters of fertility. Among all, myo-inositol (myo-ins) represents a safe compound that proved useful in issues related to fertility and pregnancy. In fact, myo-ins participates in several signaling processes, including the pathways of insulin and gonadotropins, and, therefore, it is likely to positively affect fertility. In particular, several clinical trials demonstrate that its administration can have therapeutic effects in infertile women, and that it can also be useful as a preventive treatment during pregnancy. Particularly, myo-ins could prevent the onset of neural tube defects and the occurrence of gestational diabetes mellitus, promoting a trouble-free gestation. Due to the safety and efficiency of myo-ins, such a treatment may also substitute several pharmaceuticals, which are contraindicated in pregnancy.